PRECISION MEDICINE FOR RYR1-RELATED MYOPATHIES: A COMPREHENSIVE REVIEW OF GENE EDITING, PHARMACOLOGICAL INTERVENTIONS, AND SOCIETAL IMPLICATIONS - Magdalena Fidelis; Maria Wojcieszek; Katarzyna Gondek; Dominika Gacka; Agnieszka Zalewska; Aleksandra Mączyńska; Noor Alhuda Al-karawi; Paulina Kędziorek; Zuzanna Tanç (International Journal of Innovative Technologies in Social Science, 2026)
Ryanodine receptor 1-related myopathies (RYR1-RM) constitute the most prevalent class of non-dystrophic congenital myopathies, representing a complex intersection of genetic heterogeneity, molecular pathology, and evolving therapeutic paradigms. Characterized by mutations in the RYR1 gene, these disorders manifest across a broad clinical spectrum ranging from static congenital weakness to life-threatening pharmacogenetic traits such as Malignant Hyperthermia Susceptibility (MHS). This review article provides an exhaustive synthesis of the scientific and societal landscape of RYR1-RM as of 2025. We provide a deep mechanistic analysis of the RyR1 channel’s structure-function relationship, elucidated through recent cryo-electron microscopy breakthroughs that define the "leaky channel" pathophysiology. We critically evaluate the emerging pharmacological arsenal, including the landmark Phase 1b trial of the Rycal compound ARM210 (S48168), the novel application of epigenetic modulation via 5-aza-2’-deoxycytidine, and the repurposed utility of dantrolene and salbutamol. Furthermore, we dissect the frontier of precision genetic engineering, detailing the mechanics and efficacy of Prime Editing and Twin Prime Editing strategies, alongside the development of myotropic viral vectors (MyoAAV) designed to overcome the delivery barriers inherent to the massive RYR1 gene. Beyond the bench, this report integrates a rigorous social science perspective, analyzing the health economic frameworks (ICER, QALYs) that govern access to orphan drugs, the ethical dimensions of somatic gene editing for non-lethal disabilities, and the transformative role of patient advocacy in the rare disease ecosystem. This multidimensional review aims to serve as a foundational resource for clinicians, researchers, and policymakers navigating the complex transition from supportive care to disease-modifying precision medicine.